2006
DOI: 10.1007/s00210-006-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of acute inflammation by a chitin-binding lectin from Araucaria angustifolia seeds via mast cells

Abstract: The effects of a lectin (AaL) from seeds of Araucaria angustifolia were investigated in the model of rat paw edema. In vivo anti-and pro-inflammatory activities, role of sugar residues, inflammatory mediators and systemic toxicity were assessed. Intravenous injection of AaL (0.1-1 mg/kg) dose-dependently inhibited the dextran-induced increase in edema and vascular permeability, which were prevented by association of the lectin with its binding sugar N-acetyl-glucosamine (Glyc-Nac). AaL also significantly inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…In the carrageenan-induced peritonitis model, the pinhão lectin injected intravenously at the doses of 0.1 and 1 mg/kg inhibited neutrophil migration by 69% and 92%. Mota et al (2006) studied the effects of the lectin from A. angustifolia seeds in a rat paw edema model and observed that intravenous injection of lectin (0.1-1 mg/kg) dose-dependently inhibited the increase in vascular permeability and edema induced by dextran and serotonine. This action was due to the association of the lectin with the Nacetyl-glucosamine (Glyc-NAc) binding domain.…”
Section: Lectins From Pinhãomentioning
confidence: 99%
See 1 more Smart Citation
“…In the carrageenan-induced peritonitis model, the pinhão lectin injected intravenously at the doses of 0.1 and 1 mg/kg inhibited neutrophil migration by 69% and 92%. Mota et al (2006) studied the effects of the lectin from A. angustifolia seeds in a rat paw edema model and observed that intravenous injection of lectin (0.1-1 mg/kg) dose-dependently inhibited the increase in vascular permeability and edema induced by dextran and serotonine. This action was due to the association of the lectin with the Nacetyl-glucosamine (Glyc-NAc) binding domain.…”
Section: Lectins From Pinhãomentioning
confidence: 99%
“…Thus, the pinhão lectin exerts anti-and pro-edematogenic actions by interactions with its specific domain. These actions may share a common pathway involving both the activation and inhibition of inflammatory mediators of resident mastocytes (Mota et al, 2006).…”
Section: Lectins From Pinhãomentioning
confidence: 99%
“…Paw volume was measured immediately before subcutaneous (s.c.) injection of inflammatory stimuli (0 min) into the hind paw of rats and at selected time intervals thereafter (0.5, 1, 2, 3, 4 and 5 h) by hydroplethysmometry (PanLab, LE 7500) (Mota et al, 2006). Results were expressed as increase or reduction in paw volume (mL) calculated by subtracting the basal volume measured at 0 min.…”
Section: Paw-edema Modelmentioning
confidence: 99%
“…Intravenous injection of lectin (0.01, 0.1 and 1 mg/kg) prior carrageenan reduced paw edema inhibiting the cellular event of acute inflammation via carbohydrate site interaction [59]. In another study, Mota et al [60] have described the effects of a lectin (N-acetyl-glucosamineligant) from A. angustifolia seeds in the same model of paw edema in rats, and the anti-inflammatory and pro-edematogenic actions were evaluated. Intravenous injection of lectin (0.1 and 1 mg/kg) inhibited the dextran-induced edema and vascular permeability, which were prevented by association of the lectin with its binding sugar N-acetyl-glucosamine.…”
Section: Anti-inflammatory and Antiedematogenic Activitiesmentioning
confidence: 99%
“…Lectin also inhibited edema induced by serotonin. The mechanism associated with anti-inflammatory and pro-edematogenic actions appears to be involved in a common pathway to activation or inhibition of inflammatory mediators from resident mast cells [60].…”
Section: Anti-inflammatory and Antiedematogenic Activitiesmentioning
confidence: 99%